Exploring discordant low amyloid beta and high neocortical tau positron emission tomography cases. Issue 1 (26th August 2022) - Krishnadas, Natasha; Doré, Vincent; Laws, Simon M.; Porter, Tenielle; Lamb, Fiona; Bozinovski, Svetlana; Villemagne, Victor L; Rowe, Christopher C.
Abstract: Introduction: Neocortical 3R4R (3‐repeat/4‐repeat) tau aggregates are rarely observed in the absence of amyloid beta (Aβ). 18 F‐MK6240 binds specifically to the 3R4R form of tau that is characteristic of Alzheimer's disease (AD). We report four cases with negative Aβ, but positive tau positron emission tomography (PET) findings. Methods: All Australian Imaging, Biomarkers and Lifestyle study of aging (AIBL) study participants with Aβ ( 18 F‐NAV4694) and tau ( 18 F‐MK6240) PET scans were included. Centiloid <25 defined negative Aβ PET (Aβ–). The presence of neocortical tau was defined quantitatively and visually. Results: Aβ– PET was observed in 276 participants. Four of these participants (one cognitively unimpaired [CU], two mild cognitive impairment [MCI], one AD) had tau tracer retention in a pattern consistent with Braak tau stages V to VI. Fluid biomarkers supported a diagnosis of AD. In silico analysis of APP, PSEN1, PSEN2, and MAPT genes did not identify relevant functional mutations. Discussion: Discordant cases were infrequent (1.4% of all Aβ– participants). In these cases, the Aβ PET ligand may not be detecting the Aβ that is present.